PROBABILISTIC ESTIMATION OF DISTRIBUTIVE ELECTRIC NETWORKS - Valeriy Marugin; Vilena Peyzel; Petr Revenko; Aleksandr Stepanov (Вестник Северо-Кавказского федерального университета)
The considered formulation of the problem of state estimation of electrical distribution network 6-35 kV as a problem of determination ofprobabilistic characteristics of mode parameters. For these networks, which from the point of view of traditional views, unobservable, it is proposed to introduce the concept ofprobability (confidence) observability, meaning the ability of the system to provide information about the current state in the form of confidence intervals of the modal parameters corresponding to a certain probability. The proposed design expressions for the mathematical expectations and standard errors of performance parameters of the network, and an algorithm for their receipt, taking into account the minimization of the objective function of the sum of least squares of deviations of measured and calculated values.